2010
DOI: 10.3922/j.psns.2010.1.010
|View full text |Cite
|
Sign up to set email alerts
|

Normative data and construct validity of the Rey Auditory Verbal Learning Test in a Brazilian elderly population.

Abstract: The Rey Auditory Verbal Learning Test (RAVLT) is an episodic memory test that is influenced by demographic variables, such as age, education, and gender. Classic word list learning has also been well documented to be an experimental cognitive paradigm that is very useful for the detection of Alzheimer's disease. The present study analyzed the performance of healthy elderly subjects on the RAVLT, describing the effects of age, education, and gender. To verify its construct validity, the RAVLT was compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
(62 reference statements)
2
26
1
1
Order By: Relevance
“…Unlike previous studies 9, 11 , there has not been found significant influence of formal education on test scores. This fact can be explained by the homogeneity of the participants assessed in terms of formal education, and the unequal distribution of subjects at 4 and 8 years of education, which is a limitation of this study.…”
Section: Discussioncontrasting
confidence: 53%
See 4 more Smart Citations
“…Unlike previous studies 9, 11 , there has not been found significant influence of formal education on test scores. This fact can be explained by the homogeneity of the participants assessed in terms of formal education, and the unequal distribution of subjects at 4 and 8 years of education, which is a limitation of this study.…”
Section: Discussioncontrasting
confidence: 53%
“…However, the present results cannot be generalized to the entire elderly population, being required further studies about the influence of factors such as education and depressive symptoms in more heterogeneous samples in order to increase the external validity of these findings. In this regard, we emphasize that the growing volume of studies to obtain normative parameters and applicability of neuropsychological tests for different segments of the Brazilian population 7,8,11,14,19 must be accompanied by studies on the psychometric properties of these instruments. This initiative will support the refinement of the use of these instruments for both clinical practice and research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations